Optimization of chilled and cooling water systems in a centralized utility hub - Leong, Yik T. (Animo Repository, 2014)
Process cooling is widely applied in various petrochemical and chemical industries. A chilled/cooling water system (CCWS) consists of a set of operations which usually operate in parallel configuration along with heat exchangers (HE) and chiller/cooling towers. A parallel arrangement of the CCWS would mean the process streams receive cooling utility at the supply temperature while series arrangement allow returned chilled/cooling water to be reused instead of directly sent to chiller/cooling tower. Also, parallel configurations have reduced cooling efficiency from large, thermodynamically unfavorable temperature differences. Previous studies on CCWS have dealt with cooling water and chilled water systems separately. The main aim of this study is to develop a procedure for the synthesis of an integrated CCWS in an eco-industrial park (EIP). A centralized utility hub is proposed to supply the cooling utility to the EIP. Few case studies are used to illustrate the model. Cooling/chilled water at variable supply temperature to accommodate the cooling requirement in different contiguous plants. The integration between cooling towers and chillers provides intermediate re-cooling to the process streams provides dual savings in terms of energy and operating cost. © 2014 The Authors.